PENGGUNAAN MEDIA AUDIO VISUAL DALAMPEMBELAJARAN MENYIMAK CERPEN SISWAKELAS IX SMP SWASTA BNKP TELUKDALAM - Asya Citra Zendrato (Universitas Nias Raya, 2025)
This examination is spurred by the utilization of general media in figuring out how to pay attention to brief tales. This exploration plans to determine the utilization of general media in figuring out how to pay attention to brief tales for class IX understudies at BNKP Teluk Dalam Private Center School for the 2023–2024 scholarly year. The exploration technique utilized is subjective, to be specific, an examination that endeavors to find and portray narratively the exercises completed and the effect of the moves initiated on their lives. The instrument utilized in this exploration is a composed test, specifically a paper test. This examination involved spellbinding investigation procedures concerning the means used to recognize information, to be specific, information decrease, information show, and end and confirmation. The aftereffects of this examination show that class IX-C understudies at BNKP Telukdalam Private Center School acquired a normal score of 45, which is considered poor. In light of this classification, Indonesian language subject educators ought to utilize an assortment of learning media to further develop understudy learning results, particularly in paying attention to brief tales.